2020
DOI: 10.3390/jcm9093025
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia Index Associated with Prehospital Intubation in COVID-19 Patients

Abstract: Background: There exists a need for prognostic tools for the early identification of COVID-19 patients requiring prehospital intubation. Here we investigated the association between a prehospital Hypoxemia Index (HI) and the need for intubation among COVID-19 patients in the prehospital setting. Methods: We retrospectively analyzed COVID-19 patients initially cared for by a Paris Fire Brigade advanced life support (ALS) team in the prehospital setting between 8th March and 18th April of 2020. We assessed the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…While SpO 2 should be interpreted with caution due to the leftward shift in the oxyhemoglobin dissociation curve linked to respiratory alkalosis, it remains a simple means often used to detect hypoxemia [15]. Given the prognostic importance of timely therapeutic and orientation decisions, our study supports the use of pulse oximetry as part of rapid assessment in the event of a massive influx of COVID-19 patients [8,14].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…While SpO 2 should be interpreted with caution due to the leftward shift in the oxyhemoglobin dissociation curve linked to respiratory alkalosis, it remains a simple means often used to detect hypoxemia [15]. Given the prognostic importance of timely therapeutic and orientation decisions, our study supports the use of pulse oximetry as part of rapid assessment in the event of a massive influx of COVID-19 patients [8,14].…”
Section: Discussionsupporting
confidence: 56%
“…Prehospital SpO2 values lower than 90% are, nevertheless, generally correlated with respiratory deterioration over time [2,15]. Such patients are therefore at increased risk of sudden worsening, requiring ETI and ICU admission [8,15]. Accordingly, we found that patients who belonged to the "Low SpO2" patient group had higher respiratory rates and higher prehospital gravity scores than those who belonged to the "Normal SpO2" group.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“… Mental Health 18 Jouffroy et. al 31 Hypoxemia Index Associated with Prehospital Intubation in COVID-19 Patients Case Control Clinical care reports of COVID-19 patients cared for by regional ALS prehospital service Paris, FR ● A hypoxemia index (HI) < 1.3 correlated with a 3 fold increase in prehospital endotracheal intubation of patients with COVID-19. ● Hypoxemia index may be a reliable indicator for prehospital endotracheal intubation in respiratorily compromised patients with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…In the prehospital setting, endotracheal intubation may be required to secure a patient’s airways is some of the cases. In Paris, out of 300 consecutive COVID-19 patients, 18 (6%) were treated by endotracheal intubation by the Paris Fire Brigade Advanced Life Support teams [ 4 ].…”
Section: Introductionmentioning
confidence: 99%